Hyponatremia is associated with poor prognosis among patients with chest pain discharged from internal medicine wards following acute coronary syndrome-rule-out. Issue 2 (March 2020) - Topaz, Guy; Pereg, David; Gur, Efrat; Kitay-Cohen, Yona; Ben-Zvi, Elad; Eitan, Mayan; Benchetrit, Sydney; Cohen-Hagai, Keren
Abstract : Background: Hyponatremia is the most common electrolyte abnormality observed in clinical practice. Among patients with acute coronary syndrome (ACS), serum sodium levels are inversely associated with mortality risk. We assessed associations of serum sodium level with ACS and mortality in patients with chest pain. Methods: This retrospective cohort study used clinical data from a large, academic hospital. All adults admitted with chest pain and without hypernatremia and discharged after ACS rule-out from January 2010 through June 2016 were included. The primary endpoint was the composite of 30-day ACS and mortality. Secondary endpoints were a hospital admission due to ACS and mortality in the first year following discharge. Results: Included were 12 315 patients (mean age 58.2 ± 13 years, 60% male). Patients were classified according to the serum sodium (Na) level: hyponatremia, defined as less than 135 mEq/L ( n = 289, 2.3%); 140 > Na ≥ 135 mEq/L ( n = 8066, 65.5%), and 145 > Na ≥ 140 mEq/L ( n = 3960, 32.2%). Patients with serum sodium more than 145 mEq/L were excluded. Among patients with hyponatremia, low-normal, and high-normal levels, rates of the composite outcome of unadjusted 30-day all-cause mortality and ACS admission were 4.5, 1.0, and 0.7%, respectively ( P < 0.001). Unadjusted one-year ACS rates were 3.8, 1.5, and 1.4%, respectively ( P < 0.01). Conclusion: Hyponatremia is associated with higher mortality and ACS risk among patients with chest pain who were discharged from internal medicine wards following ACS-rule-out. Sodium level may be included in the risk stratification of patients with chest pain.